MoS2/WS2 Quantum Dots as High‐Performance Lubricant Additive in Polyalkylene Glycol for Steel/Steel Contact at Elevated Temperature. Issue 1 (23rd November 2017) - Wu, Xinhu; Gong, Kuiliang; Zhao, Gaiqing; Lou, Wenjing; Wang, Xiaobo; Liu, Weimin
Abstract: Herein, molybdenum disulfide (MoS2 ) and tungsten disulfide (WS2 ) quantum dots (QDs) are prepared by a facile and green technique, and characterized by microscopy and spectroscopy. The resulting products display exceptional stability in polyalkylene glycol (PAG) base oil, and are used for the first time as friction reducing and antiwear additives in PAG for steel/steel contact. Tribological measurements indicate that the stable dispersion consisting of PAG mixed with MoS2 /WS2 QDs exhibits significant tribological properties compared with pure PAG and PAG containing MoS2 /WS2 QDs nanosheets under different loads at elevated temperatures. The excellent tribological behaviors of MoS2 /WS2 QDs are attributed to the formation of a boundary lubrication film, which can be generated not only by the physical entrapment of MoS2 /WS2 QDs at the ball‐disk contact surfaces, but also by tribochemical reaction between MoS2 /WS2 and the iron atoms/iron oxide species. Abstract : MoS2 /WS2 quantum dots (QDs) is used for the first time as lubricating oil additive. Benefiting from the smaller particle size and higher special surface area, MoS2 /WS2 QDs displays excellent dispersion stability in polyalkylene glycol (PAG). Tribological measurements indicate that MoS2 /WS2 QDs added in PAG can significantly improve the friction reduction and antiwear properties of the base oil at elevated temperature.